Antibacterial properties and major bioactive components of Mentha piperita essential oils against bacterial fruit blotch of watermelon. (26th August 2016) - Choi, Okhee; Cho, Su Kyung; Kim, Junheon; Park, Chung Gyoo; Kim, Jinwoo
Abstract: Plant-derived essential oil is an alternative to antibiotics, eliminating the concern of developing antibiotic-resistant bacterial strains. In this study, using the half-divided Petri plate assays, 32 volatile essential oils were screened for their antibacterial activity against Acidovorax citrulli (Acc). Sweet basil and peppermint oils were the most effective against Acc, with subsequent trials showing that peppermint oil to be the most active. Using gas chromatography–mass spectrometry, the major compositions of peppermint oil were analysed. Among the various compositions of peppermint oil, menthol, neomenthol, isopulegone and 1, 8-cineole were significantly active against Acc and each component at 0.2% concentration inhibited all bacterial growth. This study demonstrated in vitro and in vivo antibacterial activities of peppermint oil and its active components against Acc. These results suggest the use of peppermint oil as a potential antibacterial agent to treat seed with Acc.